Implementasi Edukasi Digital pada Ibu-Ibu PKK sebagai Upaya Meningkatkan Pemahaman Teknologi Informasi - Zuhriyah, Nikmatu; Nadhifah, Fadiyah; Anjani, Calya Sadira; Safitri, Safitri; Amalia, Tiana; Amalia, Zafirah Nur; Ala, Faridatul' (Pakis Journal Institute, 2026)
The rapid development of information and communication technology has significantly transformed various aspects of community life, including family literacy practices. Digital literacy has become an essential skill as it involves not only reading and writing abilities but also the capacity to access, understand, evaluate, and responsibly use digital information. In the family context, mothers play a strategic role as primary educators for children, particularly those involved in the Family Welfare Empowerment (PKK) organization. However, limited digital literacy skills and a lack of knowledge about children’s digital literacy platforms remain major challenges in the community. Therefore, this community service program aims to improve the digital literacy understanding and skills of PKK mothers through a Digital Literacy Program conducted in RW 04, Jakasetia Village. This study employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation involving 30 participants. The results indicate that the digital literacy program positively enhanced participants’ knowledge, skills, and awareness in using digital technology safely, wisely, and responsibly. Participants were also able to utilize various digital literacy platforms, such as SIBI, Literacy Cloud, and Let’s Read, to support children’s reading activities at home. This program contributes positively to strengthening family literacy and fostering a sustainable digital literacy culture within the community.